Application of Information Economics and New Information Economics - Arya Kemuning; Abdul Nasir (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
New Information Economics (NIE) is a method used to assess and plan investment systems and information technology withina company. The concept applied to this measurement is the New Information Economics concept. The role of Information Technology has become a very important factor that can help companies improve their company performance. The purpose of writing Information Economics and New Information Economics is to analyze and find out the benefits of applying Information Economics and New Information Economics on companies based on sources obtained. With the help of the informationeconomy and the new information economy, all ongoing project budget calculations, etc., can be evaluated. Be able to calculate which projects are important and which are not. The Information Economy and the New Information Economy help companies estimate the budget needed to implement a project. Can take into account the company's finances so as not to experience big losses.